2011
DOI: 10.1038/leu.2011.18
|View full text |Cite
|
Sign up to set email alerts
|

The self-association coiled-coil domain of PML is sufficient for the oncogenic conversion of the retinoic acid receptor (RAR) alpha

Abstract: In acute promyelocytic leukemia (APL) the retinoic acid receptor alpha (RARa) becomes an oncogene through the fusion with several partners, mostly with promyelocytic leukemia protein (PML), all of which have in common the presence of a self-association domain. The new fusion proteins, therefore, differently from the wild-type RARa, which forms only heterodimers with retinoic X receptor alpha, are also able to homooligomerize. The presence of such a domain has been suggested to be crucial for the leukemogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…Furthermore, the ability of the predominantly cytoplasmic PR proteins (mPR and hPR-S) to disrupt PML-NBs suggests that disruption might be an active signal-mediated process rather than just a passive architectural consequence of incorporation of the RARα domain into PML-NBs. The relevance of PML-NB disruption was also pointed out in a recent publication analyzing the minimal structural requirements of PR for leukemogenesis (26). This is in line with our model that PML-NBs represent scaffolds for assembly of active protein complexes, such as the PAX complex, at the onset of cellular senescence.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, the ability of the predominantly cytoplasmic PR proteins (mPR and hPR-S) to disrupt PML-NBs suggests that disruption might be an active signal-mediated process rather than just a passive architectural consequence of incorporation of the RARα domain into PML-NBs. The relevance of PML-NB disruption was also pointed out in a recent publication analyzing the minimal structural requirements of PR for leukemogenesis (26). This is in line with our model that PML-NBs represent scaffolds for assembly of active protein complexes, such as the PAX complex, at the onset of cellular senescence.…”
Section: Discussionsupporting
confidence: 74%
“…on May 10, 2018. by guest www.bloodjournal.org From PML-RAR-driven APL. As previously shown, 16,35 expression of PML-RAR in the preleukemic phase caused a modest defect on differentiation in vitro (supplemental Figure 11), and Hdac1 knockdown greatly augmented this effect with a strong decrease of Mac-1 confirmed previous studies 36 demonstrating that PML-RAR expression enhanced genome instability compared with WT cells (supplemental Figure 13). Hdac1 knock-down amplified this phenomenon with more than 50% of metaphases being aneuploid after in vitro plating ( Figure 3D).…”
Section: Hdac1 Knock-down Enhances Differentiation Block and Genomic supporting
confidence: 74%
“…Thus, individuals with the KIR2DS1 gene are susceptible to autoimmune diseases such as psoriasis and psoriatic arthritis [31,33,34] and also to a fatal outcome with Ebola virus infection [35]. However, Marin et al (2011) reported that KIR2DS1 was the only factor predicting shorter progression-free (PFS) and overall survival in chronic myeloid leukemia patients treated with Imatinib [36]. Furthermore, a negative association of the gene was reported for recurrent respiratory papillomatosis severity [37] and with scleroderma [38].…”
Section: Discussionmentioning
confidence: 97%